IDENTIFIKASI MASALAH YANG DIHADAPI GURU BIOLOGI DALAM PELAKSANAAN PEMBELAJARAN PADA MATERI EKOSISTEM - Dian Aswita (Universitas Islam Negeri Ar-Raniry, 2015)
The purpose of this research is to identify the problems encountered by biology teacher in implementing ecosystem material in learning teaching. The problem comes from various factors, they were from the teachers themselves, the students’ readiness in accepting the materials, material development that has been used as well as supporting facilities required during the learning process. The data were collected by observation and documentation method. The result showed that the learning process was not effective yet and the students were relatively passive, the learning process was considered less fun. Hopefully the implementation of the material will involve simple practical activities.